Morphological and Ultrastructural Characteristics of Tea Mosquito Bug Antennae, Helopeltis theivora Waterhouse (Hemiptera: Miridae) from Hainan, China - Wenhui Li; Yonglin Liao; Zhufeng Lin; Xuncong Ji; Qi Yao (Insects)
The tea mosquito bug, Helopeltis theivora Waterhouse, (Hemiptera: Miridae) is a significant sap-sucking pest in tropical tea plantations that causes substantial losses in tea production on Hainan Island, China. The morphological and ultrastructural characteristics of H. theivora antennae have not been elucidated. Here, we used several microscopy techniques (SDM, SEM, and TEM) to investigate the morphology as well as the setae and sensilla on the antennae of nymphs and adults of H. theivora. SDM observations indicated that the antennae of H. theivora were filamentous in shape and included four segments: scape, pedicel, flagellum I, and flagellum II. The length of the antenna was approximately twice that of the body and the setae were enriched in flagellum II. The SEM results showed that there were a total of six types of sensilla on the antenna of H. theivora, including the sensilla chaetica (SCh), sensilla trichoidea (ST), sensilla basiconica (SB), sensilla coeloconica (SCo), sensilla mammilliformia (SM), and Böhm’s bristles (BB). In particular, there were three subtypes (I, II, and III) of different lengths in SCh and SB, and two subtypes of straight (I) and curved (II) sensilla in ST. The TEM results indicated that diverse internal structures were present in SCh, ST, SB, and SCo, suggesting different functions and different sensory mechanisms of these four main sensilla in the orientation behavior of H. theivora on tea plants. These findings provide a theoretical basis for further exploration of the olfactory orientation of H. theivora in tropical tea plantations and pave the way for the development of semiochemical-based control options in the future.